Masa Depan Kehidupan Beragama dan Kearifan Budaya Lokal: Studi terhadap Pemikiran Abdurrahman Wahid Mengenai Asal Usul Peradaban Islam dan Implikasinya Di Masa Mendatang - M. Shofiyyuddin (UIN Sunan Kalijaga Yogyakarta, 2012)
This article elaborates abdurrahman wahid’s concept about the origin of islamic civilization. Islam humanist, in the view of gusdur, is the view of history that describes so close to reality in past. History that is not to see the past in mythic and humanity. Someone’s view of the past as it is, is going to determine one’s outlook on the future. Respect and careful consideration based on factual condition of socity is formed by knowledge and concept about the history around him. Finally, Islam humanist is Islam that remarkes human rights, fair and equal before the law, defending minority, and also toleration to the local wisdom or native ways of religion.